2012
DOI: 10.1038/onc.2012.251
|View full text |Cite
|
Sign up to set email alerts
|

CFTR suppresses tumor progression through miR-193b targeting urokinase plasminogen activator (uPA) in prostate cancer

Abstract: Cystic fibrosis (CF) transmembrane conductance regulator (CFTR) is expressed in the epithelial cells of a wide range of organs/tissues from which most cancers are derived. Although accumulating reports have indicated the association of cancer incidence with genetic variations in CFTR gene, the exact role of CFTR in cancer development and the possible underlying mechanism have not been elucidated. Here, we report that CFTR expression is significantly decreased in both prostate cancer cell lines and human prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
90
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 40 publications
3
90
1
Order By: Relevance
“…Besides, defective or dysregulated CFTR can activate NF-B, which has been demonstrated to be one of the major transcriptional factors to activate miRNAs [71,72]. Interestingly, we have also found that CFTR knockdown leads to enhanced activation of NFB in cancer cell lines [95]. In addition, we have shown that NFB inhibitor reverses CFTR knockdown-enhanced cancer progression [95].…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…Besides, defective or dysregulated CFTR can activate NF-B, which has been demonstrated to be one of the major transcriptional factors to activate miRNAs [71,72]. Interestingly, we have also found that CFTR knockdown leads to enhanced activation of NFB in cancer cell lines [95]. In addition, we have shown that NFB inhibitor reverses CFTR knockdown-enhanced cancer progression [95].…”
mentioning
confidence: 68%
“…Interestingly, CFTR-mediated HCO 3  transport has been shown to activate a soluble form of adenylyl cyclase and cAMP-dependent pathway in sperm [53] and lung epithelial cells [55], which may lead to activation of some cAMP dependent transcription factors, such as CREB, and thus transcription of related miRNAs. As discussed earlier, our recent study has shown that miRNA expression is greatly influenced by extracellular HCO3  concentration [60], and that CFTR manipulation affects miRNA expression profile in prostate cancer cell lines [95]. Besides, defective or dysregulated CFTR can activate NF-B, which has been demonstrated to be one of the major transcriptional factors to activate miRNAs [71,72].…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…We also reported the upregulation of rat miR-193b after nitrofen exposure. Others attributed cystic fibrosis transmembrane conductor regulator replenishment and cancer regression to the upregulation of miR-193b in human (17). Thus, miR-193b may rescue cystic fibrosis transmembrane conductor regulator downstream of nitrofen in rat lung hypoplasia-a finding that warrants further investigation.…”
Section: Rat Mirnas and Their Target Mrnas Could Function Similarly Tmentioning
confidence: 96%